PERTANGGUNGJAWABAN POLITIK PRESIDEN PASCA AMANDEMEN UUD 1945 - -, Hendra (Departemen Ilmu Politik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Padjadjaran, 2016)
After the UUD 1945 amendment, there is fundamental change in the Indonesian governmentalÂ system. This changes well-marked with the facts that after amandement there is an alteration to theÂ patern of president or vice president election, and the regulation of the relation between presidentÂ and DPR. This changes has influence the president political responsibility after amandement.